IMPLICATIONS OF THE COVID-19 PANDEMIC ON THE IMPLEMENTATION BUSINESS CONTRACTS - Mutia Kartika Putri (Indonesia Private Law Review, 2023)
The spread of Covid-19 has caused many debtors to be unable to carry out their achievements in contracts. The problems in this research are related to force majeure according to civil law in Indonesia, whether what is included in the qualifications for the Covid-19 pandemic can be categorized as force majeure according to Indonesian civil law and the legal consequences of the Covid-19 pandemic related to the implementation of business contracts. This type of research is normative legal research and descriptive research. The results of the study show that the characteristics of force majeure in civil law in Indonesia are not regulated in the Civil Code. Force majeure refers to events that cannot be predicted by humans or are related to natural events. The proof is that the cause of force majeure may not necessarily be categorized as force majeure. Several force majeure characteristics must be met as a reason for force majeure due to the Covid-19 pandemic by the debtor. This shows that the use of force majeure reasons still has a heavy burden and responsibility on the part of the debtor, there are restrictions on the application of force majeure. There are also incidents in the form of the Covid-19 pandemic or government policies that arose as a result of the Covid-19 pandemic. It needs to be reviewed based on the nature of force majeure and the need for propriety or good faith of the debtor even though an event hinders the fulfillment of achievements.